Desire of student to enter UMPSA fulfilled, receives funding throughout study - Muhammad Aizat, Azed (UMPSA, 2023)
JERTEH, TERENGGANU, 25 September 2023 - The desire of Sekolah Menengah Kebangsaan Tok Dor’s leaver, Nooraizah Mohd Safie, 19, to go to the university was fulfilled after almost forgoing the opportunity to continue studying thinking about the fate of her family that is unable to support her due to life difficulties and financial constraints.